Higher dietary protein intake preserves lean body mass, lowers liver lipid deposition, and maintains metabolic control in participants with long‐chain fatty acid oxidation disorders. Issue 5 (24th July 2019) - Gillingham, Melanie B.; Elizondo, Gabriela; Behrend, Annie; Matern, Dietrich; Schoeller, Dale A.; Harding, Cary O.; Purnell, Jonathan Q.
Abstract: Medical nutrition therapy for long‐chain fatty acid oxidation disorders (LC‐FAODs) currently emphasizes fasting avoidance, restricted dietary long‐chain fatty acid intake, supplementation with medium chain triglycerides, and increased carbohydrate intake. We hypothesize that increasing dietary protein intake relative to carbohydrate intake would preserve metabolic control yet induce physical benefits including reduced hepatic lipogenesis. Therefore, we compared two dietary approaches with similar fat intake but different carbohydrate to protein ratios in participants diagnosed with LC‐FAODs. Thirteen participants were enrolled and randomized into either a high‐protein (PRO) or a high‐carbohydrate (CHO) diet for 4 months. Baseline and 4‐month assessments included body composition, ectopic lipid deposition, and resting energy expenditure. End of study assessments also included total energy expenditure, metabolic responses to oral feedings, and whole‐body fatty acid oxidation capacity. At the end of the dietary intervention, both groups had similar energy expenditure, fat and glucose oxidation rates, and glucolipid responses to mixed meal and oral glucose loads. Neither dietary group experienced worsening symptoms related to their LC‐FAOD. Compared to the CHO group, the PRO group exhibited increased blood levels of short‐chain acylcarnitines, reduced intrahepatic lipid content, and maintained lean body mass while the CHO group lost lean mass. In patients with LC‐FAODs, increasing protein intake maintained metabolic control, reduced liver fat without risk of metabolic decompensation, and helped preserve lean body mass. We propose that a modest increase in dietary protein along with fasting avoidance and fat restriction may improve body composition and energy expenditure in patients with LC‐FAODs.